2019
DOI: 10.3390/ijerph16111891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dehydration and Rehydration on Cognitive Performance and Mood among Male College Students in Cangzhou, China: A Self-Controlled Trial

Abstract: Water accounts for 75% of brain mass. Associations may exist between hydration and cognitive performance. The objective of this study was to investigate the effects of dehydration and rehydration on cognitive performance and mood. In this self-control trial, 12 men were recruited from a medical college in Cangzhou, China. After 12 h of overnight fasting, the participants took baseline tests at 8:00 AM on day 2. First morning urine and blood osmolality were analyzed to determine hydration state. Height, weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 42 publications
5
39
1
3
Order By: Relevance
“…Consistent with the current findings, a study conducted among young adults after water restriction for 12 h demonstrated that alertness increased after drinking 300 mL of water [48]. Another study with 12 young adults revealed that 1500 mL water supplementation attenuated the decrements of dehydration, including vigor, fatigue, and TMD [23]. A systematic analysis concluded that mood, including feelings of alert or calm, was positively influenced by water supplementation [49].…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with the current findings, a study conducted among young adults after water restriction for 12 h demonstrated that alertness increased after drinking 300 mL of water [48]. Another study with 12 young adults revealed that 1500 mL water supplementation attenuated the decrements of dehydration, including vigor, fatigue, and TMD [23]. A systematic analysis concluded that mood, including feelings of alert or calm, was positively influenced by water supplementation [49].…”
Section: Discussionsupporting
confidence: 85%
“…Insufficient water intake may lead body into dehydration. Researches have shown that dehydration can impair the physical [4,5] and cognitive performances [6,7], which included vigilance attention [8], working memory [9,10] and executive function [11]. Moreover, dehydration may also have deleterious effects om cardiovascular health [12].…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining an adequate state of hydration is vital for optimizing human health and performance. Previous literature assessing the role of hydration on exercise performance has demonstrated the detrimental impact of acute hypohydration on aerobic [ 1 , 2 , 3 ] and anaerobic [ 4 , 5 , 6 , 7 ] exercise performance, as well as cognitive function [ 8 , 9 , 10 , 11 ]. In recent years, the focus has shifted from the short-term impact of hypohydration on exercise and cognitive performance to the role that inadequate fluid intake, also termed underhydration [ 12 ], has on health-related outcomes such as obesity [ 3 , 13 , 14 , 15 , 16 , 17 , 18 ], diabetes [ 19 , 20 , 21 ], and chronic kidney disease [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%